Studi Eksperimental Hubungan Feeding di Mesin Bubut CMZ T-360 dengan Kekasaran Permukaan Material St 60 untuk Shaft Steady Rest - Kurniawan, Agus; Samudra, Yudha; Nugroho, Eko Prasetyo; Eleganta, Florent Reno; Ganang, Gabriel; Krisnata, Hindi Chandra; Faturrahman, Ichsan (Universitas Muhammadiyah Yogyakarta, 2020)
The research tested the effects between feeding and surface roughness on shaft of steady rest which will be worked in CMZ T-360’s lathe machine. Material of St.60 was turned into shaft of steady rest in 2 CMZT-360’s machines with several of feeding like 0.045, 0.056, 0.068, 0.079, 0.90 and 0,102 mm/rev. Then the work piece was tested the surface roughness of the work piece with using roughness tester and being seen the shape of the surface with using photo macro. The result of the roughness’s test showed that CMZ-T360’s lathe machine could reach Ra 1.55 µm until 4.79 µm with several of feeding. The work piece would be assembled in steady rest and being used to support 58 kg weigth in 2 hours to know the effect of surface roughness. After testing on steady rest, would be done photo macro on the specimen to make easy on visual analysis. From the data which is obtained can conclude that feeding variation which used on this research not so affecting the quality of surface roughness of the workpiece, the value of surface roughness that resulted from this research is mostly N8 (3,25 µm- 5,29 µm) and only a few that valued N7 (1,55 µm-2,53 µm) . The second conclusion is the surface roughness which quickly wornt-out after assembled at steady rest is the rough surface (4,79 µm become 3,84 µm) compared with the smooth surface (2,23 µm become 2,03 µm).